"It'll never end, I'll never go": representation of caregiving in Samuel Beckett's Endgame and Footfalls - Chiang, Michelle Hui Ling (2023)
Research on the unrepresentability of death in Samuel Beckett's oeuvre abound in Beckett scholarship, but little attention has been given to the artist's representation of caregiving to the dying in his plays. With reference to Martin Heidegger's concept of care and Albert Camus's idea of the absurd, this article analyzes Endgame (1957) and Footfalls (1976) by attending to Beckett's dramatic representation of caregiving as undergirded by a sense of its absurdity. The almost 20-year gap between the writing of both plays highlights the development of an understanding that this sense of absurdity is never about the caregiver's questioning of one's obligation to the dependent but about how one chooses to respond to caregiving as an absurd predicament. The pertinence of such a representation of caregiving by Beckett lies in its poignant articulation of a complex experience that is often left unexpressed by caregivers who prioritize their dependent loved ones over themselves.